2015
DOI: 10.1093/femsec/fiv073
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition and diversity in an ancestral ant fungus symbiosis

Abstract: Fungus-farming ants (Hymenoptera: Formicidae, Attini) exhibit some of the most complex microbial symbioses because both macroscopic partners (ants and fungus) are associated with a rich community of microorganisms. The ant and fungal microbiomes are thought to serve important beneficial nutritional and defensive roles in these symbioses. While most recent research has investigated the bacterial communities in the higher attines (e.g. the leaf-cutter ant genera Atta and Acromyrmex), which are often associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 80 publications
8
73
1
1
Order By: Relevance
“…[11,39]) and microbiome convergence has also been noted in some, but not all, leaf-cutter ant symbioses (e.g. [40,41]). Pratte et al [31] recently demonstrated changes in microbiome composition between anemone-hosting and non-hosting A. clarkii clownfish in a laboratory setting, implying either direct microbial transfer from anemone to clownfish or a shift in microbial diversity in response to the interaction.…”
Section: Resultsmentioning
confidence: 96%
“…[11,39]) and microbiome convergence has also been noted in some, but not all, leaf-cutter ant symbioses (e.g. [40,41]). Pratte et al [31] recently demonstrated changes in microbiome composition between anemone-hosting and non-hosting A. clarkii clownfish in a laboratory setting, implying either direct microbial transfer from anemone to clownfish or a shift in microbial diversity in response to the interaction.…”
Section: Resultsmentioning
confidence: 96%
“…Members of Îł-Proteobacteria were found in the attine ant abdomens but only in traces and then primarily in the rectum (Figure 2). This finding is of interest because representatives of Îł-Proteobacteria have repeatedly been reported as being abundant in the fungus gardens of attine ants (Aylward et al, 2014(Aylward et al, , 2012Kellner, Ishak, Linksvayer, & Mueller, 2015;Pinto-TomĂĄs et al, 2009), although it remains unclear whether these were the same OTUs or not. These previously reported Îł-Proteobacteria are mostly Enterobacteriaceae with abilities to fix nitrogen in laboratory fungus gardens of Atta leaf-cutting ants (Pinto-TomĂĄs et al, 2009).…”
Section: Myr Ednaella Workers (Supporting Informationmentioning
confidence: 85%
“…Several studies used next-generation sequencing approaches to characterize microbiomes from fungus gardens of leafcutter ants (Suen et al, 2010;Aylward et al, 2012;Aylward et al, 2014) and non-leafcutter attine species (Sen et al, 2009;Ishak et al, 2011;Liberti et al, 2015;Kellner et al, 2015). These studies documented the presence of a great bacterial diversity in attine gardens (e.g., Enterobacter, Pseudomonas, Klebsiella, Pantoea and others), and Aylward et al (2012) investigated the potential functions of bacteria in Atta gardens using meta-proteomic analyses.…”
Section: Introductionmentioning
confidence: 99%